Delayed Diagnosis, Difficult Decisions: Novel Gene Deletion Causing X-Linked Hypophosphatemia in a Middle-Aged Man with Achondroplastic Features and Tertiary Hyperparathyroidism - Yun Ann Chin; Yi Zhao; Gerald Tay; Weiying Sim; Chun Yuen Chow; Manju Chandran (Case Reports in Endocrinology)
X-linked hypophosphatemia (XLH) is the most prevalent form of hereditary hypophosphatemic rickets associated with phosphate wasting. However, its diagnosis is often missed, resulting in patients presenting late in the course of the disease when complications such as tertiary hyperparathyroidism and renal failure have already set in. Phosphate and calcitriol replacement, both of which have undesirable consequences of their own, have historically been the main stay of therapy. We describe the case of a 57-year-old gentleman with tertiary hyperparathyroidism, who was mislabelled as having achondroplasia for many years before we made a diagnosis of XLH in him. His XLH was found to be due to a hereto unreported deletion of entire exon 14 with partial deletions of introns 13 and 14 of the PHEX gene. Perioperative management in him was fraught with surgical and medical difficulties including an operation that was technically complicated due to his multiple anatomical deformities. Our case also highlights the critical importance of timely recognition and accurate diagnosis of XLH, as well as the long-term multidisciplinary management that is needed for this disorder.